Die "Nova Expositio" der Hanschrift Ripoll 42 : Text und Kommentar - Gümpel, Karl-Werner (Miscel·lània litúrgica catalana, 2007)
The present article deals with a revised version of the so-called Nova expositio, whose original text appeared in the anonymous Alia musica (9th/10th cent.). Written around 1030 as part of Ms. Barcelona, Arxiu de la Corona d?Aragó, Ripoll 42, it represents a tonary treatise which was probably intended for a French monastery. In Part II of the article a synoptic edition of both the revised and the original version of the Nova expositio is offered, while Part III serves to discuss the chant examples cited in the treatise.